Assessment of IT Governance Capability Level Using the COBIT 2019 Framework: A Case Study of XYZ Institution - Amry, Anshari; Wirani, Yekti; Sucahyo, Yudho Giri (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2025)
XYZ Institution recognizes Information Technology (IT) as a strategic enabler essential for achieving organizational objectives and advancing its digital transformation objectives. IT governance plays a critical role in ensuring alignment between the utilization of IT and the achievement of strategic objectives. In today"™s digital era, the presence of structured, measurable, and strategically aligned IT governance has become essential to support both operations and business goal attainment. To address this issue, the study adopts an IT governance capability level assessment approach based on the COBIT 2019 framework. The methods used include Design Factors and Goals Cascade to identify the relevant Governance and Management Objectives (GMO) tailored to the organization"™s characteristics. Following this mapping, a capability level assessment is conducted using process activity parameters defined in COBIT 2019. The results indicate that most IT governance areas have achieved a satisfactory level of capability. Four processes (EDM02, APO12, DSS04, DSS06) achieved Capability Level 5, indicating optimized performance. Eleven processes (EDM04, APO02, APO03, APO04, APO05, APO08, BAI01, BAI02, BAI03, BAI08, BAI11) achieved Capability Level 4, reflecting established and managed practices. One process (BAI05) is currently at Level 3, highlighting an opportunity that can be further developed to align with higher-performing areas. This study contributes theoretically by providing a reference for future research on IT governance capability assessment using COBIT 2019, and practically by offering recommendations to enhance IT governance practices within financial institutions. Furthermore, this study provides example of targeted recommendations for enhancing IT governance in areas requiring improvement, with the aim of supporting the XYZ Institution strategic goals. This study contributes theoretically by providing a reference.